2012
DOI: 10.17221/44/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Pollen and inorganic characteristics of Bulgarian unifloral honeys

Abstract: Atanassova J., Yurukova L., Lazarova M. (2012): Pollen and inorganic characteristics of Bulgarian unifloral honeys. Czech J. Food Sci., 30: 520-526.The melissopalynological characteristics, three main physicochemical parameters (water content, pH, and electrical conductivity), and 19 macro-and microelements contents of 15 honey types from throughout Bulgaria that were collected from 2006 to 2009 were evaluated. The main honeys studied came from Robinia pseudoacacia L., Helianthus annuus L., Brassica spp., Tili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 12 publications
7
20
0
Order By: Relevance
“…Mineral content is generally lower in blossom honeys compared to the honeydew honey, particularly for potassium and phosphorus content according to the investigations of different types of honey from northwestern Spain (Escuredo et al, 2012). The element content of Bulgarian unifloral honeys (Atanassova et al, 2012) showed that the maximum values of the macroelement potassium was recorded in chestnut, Paliurus honey and in the sample of honeydew honey (1628, 1198 and 1121 mg*kgˉ¹). P and Mg were higher in the sample of honeydew honey in comparison to all unifloral honeys investigated according to the same authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral content is generally lower in blossom honeys compared to the honeydew honey, particularly for potassium and phosphorus content according to the investigations of different types of honey from northwestern Spain (Escuredo et al, 2012). The element content of Bulgarian unifloral honeys (Atanassova et al, 2012) showed that the maximum values of the macroelement potassium was recorded in chestnut, Paliurus honey and in the sample of honeydew honey (1628, 1198 and 1121 mg*kgˉ¹). P and Mg were higher in the sample of honeydew honey in comparison to all unifloral honeys investigated according to the same authors.…”
Section: Discussionmentioning
confidence: 99%
“…Data about the mineral content of honeydew honey in Bulgaria are sporadic (Atanassova et al, 2012;Nikolova et al, 2013;Yurukova et al, 2008) and for microscopic features are almost absent.…”
Section: Introductionmentioning
confidence: 99%
“…Among the major and minor elements reported to be present in honey, K is reported to be present in the highest concentrations (Abu‐Tarboush and others ; Terrab and others ; Fernández‐Torres and others ; Dag and others ; Farooq Khan and Maqbool ), followed by Na (Nanda and others ; Santos and others ; Daniel and others ; Mbiri and others ; Moniruzzaman and others ), while Mg, Ca, Fe, Zn, and Cu are present in intermediate amounts (Tuzen and Soylak ; Dag and others ; Belouali and others ; Vit and others ; Atanassova and others ; Mondragón‐Cortez and others ). Although the stated amount of minerals found in honeys is shown in apparently low percentage when compared with other honey constituents, some precise elements are found in similar or even higher amounts than some common fruits and vegetables.…”
Section: Methods Of Reviewmentioning
confidence: 96%
“…The ranking of average pollen concentrations for the honeys studied was Brassica > Helianthus > Tilia > Robinia (3).…”
Section: Pollen Analysismentioning
confidence: 98%